THE EFFECT OF RELATIONSHIP QUALITY OF WORK LIFE, QUALITY OF HUMAN RESOURCES ON ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) : AN INDUSTRIAL PSYCHOLOGY STUDY - Purwani, Widio; Sukestiningsih, Sukestiningsih (Jurnal Ilmiah Manajemen, Ekonomi, & Akuntansi (MEA), 2022)
This study aimed to examine the link between Quality of Work Life, Quality of Human Resources, and Organizational Citizenship Behavior (OCB) in Jakarta's textile industries. This study employs quantitative methods. This study includes both primary and secondary data types. The distribution of questionnaires to 50 respondents yielded preliminary data, whilst the literature review yielded secondary data. 50 employees of firm X, which is engaged in the fabric sector in Jakarta, participated in this study. The data processing in this study uses a validity test, reliability test, regression equation analysis, regression coefficient, and partial hypothesis testing (f-test), then decision making. Based on the results of the research in the study, it can be concluded that the two variables used as independent variables in the study, namely Quality Work-Life and Quality of Human Resources, were proven to have an influence on Organizational Citizenship Behavior in fabric companies in Jakarta, but the effect was not significant.